In Situ Biphasic Extractive Fermentation for Hexanoic Acid Production from Sucrose by Megasphaera elsdenii NCIMB 702410 - Choi, Kieun; Jeon, Byoung Seung; Kim, Byung-Chun; Oh, Min-Kyu; Um, Youngsoon; Sang, Byoung-In (Humana Press, Inc., 2013)
Hexanoic acid production by a bacterium using sucrose as an economic carbon source was studied under conditions in which hexanoic acid was continuously extracted by liquid-liquid extraction. Megasphaera elsdenii NCIMB 702410, selected from five M. elsdenii strains, produced 4.69 g l(-1) hexanoic acid in a basal medium containing sucrose. Production increased to 8.19 g l(-1) when the medium was supplemented by 5 g l(-1) sodium butyrate. A biphasic liquid-liquid extraction system with 10 % (v/v) alamine 336 in oleyl alcohol as a solvent was evaluated in a continuous stirred-tank reactor held at pH 6. Over 90 % (w/w) of the hexanoic acid in a 0.5 M aqueous solution was transferred to the extraction solvent within 10 h. Cell growth was not significantly inhibited by direct contact of the fermentation broth with the extraction solvent. The system produced 28.42 g l(-1) of hexanoic acid from 54.85 g l(-1) of sucrose during 144 h of culture, and 26.52 and 1.90 g l(-1) of hexanoic acid was accumulated in the extraction solvent and the aqueous fermentation broth, respectively. The productivity and yield of hexanoic acid were 0.20 g l(-1) h(-1) and 0.50 g g(-1) sucrose, respectively.